Congenital Orbital Glial Heterotopia Associated with Clinicopathological Anophthalmia: A Case Report - Reyes-Godinez, Natalia; Tamez-Tamez, Veronica E.; Ruiz-Lozano, Raul E.; Chavez-Cobian, Stephania; Gonzalez-Murillo, Eduardo; Villarreal-Reyes, Lauro Arturo (Klinische Monatsblätter für Augenheilkunde, 2022)
Glial heterotopia (GH) is the presence of glial tissue outside the cranial cavity, without communication with the brain. The orbital location usually presents as eyelid swelling, strabismus, and proptosis. This is considered a congenital location that usually presents at birth. Its association with anophthalmia is uncommon. We report the case of a 2-day-old male neonate with left congenital intraorbital lesion presenting with massive proptosis. No eyeball could be seen. Preoperative magnetic resonance imaging disclosed a large and predominantly cystic mass occupying and protruding from the left orbit without intracranial extension. In the operating theatre, a large amount of fluid was aspirated prior to total resection of the mass. Chemical analysis of the fluid was compatible with cerebrospinal fluid. Histologically, the tumor was composed of mature neuroglial tissue and ependymal cells. Despite multiple sections, no choroid plexus or intraocular content was found. The diagnosis of GH with anophthalmia was made.
Keywords: anophthalmia; cerebrospinal fluid; glial heterotopia; orbit; surgical resection